2023
DOI: 10.26434/chemrxiv-2023-gkfl8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Paradigm Shift in Catalysis: Electro- and Photomediated Nickel-Catalyzed Cross-Coupling Reactions

Abstract: Transition-metal cata-lyzed cross-coupling reactions are fundamental reactions in organic chemistry, facilitating strategic bond formations for accessing natural products, organic mate-rials, agrochemicals, and pharmaceuticals. Redox chemistry enables access to elusive cross-coupling mechanisms through single-electron processes as an alternative to classical two-electron strategies, which are predominated by palladium catalysis. The hallmark of this redox platform is the systematic modulation of transition-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Despite this, a range of other electron-rich arylzinc nucleophiles (Scheme , 53l – 53n ), and heteroaryl species ( 53o, 53p ) were compatible. The success of electron-rich aryl coupling partners is significant given that these fragments are often unsuccessful using alternative reductive cross-coupling strategies involving aryl halides and tertiary aliphatic radical precursors . In cases were electron-neutral (hetero)­arylzinc reagents gave lower yields, we found that the desired product could be obtained in higher quantities if p -methoxyphenyl thionoester 54a was used as the redox-active starting material instead of 51b …”
Section: Section 2: Ni-catalyzed Cross-couplings Of Thiocarbonyl-acti...mentioning
confidence: 92%
“…Despite this, a range of other electron-rich arylzinc nucleophiles (Scheme , 53l – 53n ), and heteroaryl species ( 53o, 53p ) were compatible. The success of electron-rich aryl coupling partners is significant given that these fragments are often unsuccessful using alternative reductive cross-coupling strategies involving aryl halides and tertiary aliphatic radical precursors . In cases were electron-neutral (hetero)­arylzinc reagents gave lower yields, we found that the desired product could be obtained in higher quantities if p -methoxyphenyl thionoester 54a was used as the redox-active starting material instead of 51b …”
Section: Section 2: Ni-catalyzed Cross-couplings Of Thiocarbonyl-acti...mentioning
confidence: 92%